Comparing early oral feeding with traditional oral feeding in upper gastrointestinal surgery - Seyed Nejat HOSSEINI; Seyed Nouraddin MOUSAVINASAB; Haleh RAHMANPOUR; Somayeh SOTODEH (Turkish Journal of Gastroenterology, 2019)
-